THE FIRST MINISTER OF HEALTH OF THE KYRGYZ ASSR, KOZHOKAN SHORUKOV - Kanimetov A.; Kachkynova E. (Vestnik Issyk-Kulʹskogo universiteta)
This article tells about Kozhokan Shorukov, one of the outstanding son of the Kyrgyz people, and Soviet activist, the first Kyrgyz minister of health. It is said that he spent his childhood in the Karakol region and served the family of Ivanov, the head of the Karakol district, and studied with his children in a Russian-native school, learning to read, write, and speak Russian. Kozhokan's journey in life, the great works he left in the pages of history will continue to be mentioned in the pages of history. It is recorded that he directly worked for the opening of special secondary medical schools in the cities of Osh, Naryn, Karakol, Jalal-Abad and Tokmok, which were the capitals of the region, during his work in the field of health care. During his tenure as People's Commissar of Health Care, the opening of maternity homes, paramedic departments, doctors' offices and a number of hospitals took place under the leadership of Kozhokan Shorukov.